The technique of laboratory tests to determine the filtration coefficient of sandy soils to assess the safety in the operation of sludge storage tanks - Kasperov, Георгий; Levkevich, Виктор; Pastukhov, Сергей; Kukshinov, Михаил; Buzuk, Александр; Mikanovich, Дмитрий; Kobyak, Валерий (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2015)
For the purpose of forecasting the occurrence of emergencies on hydraulic structures the experimental facility Darcy-device has been improved and the methods of laboratory studies aimed at the determination of basic parameters of fluid filtration through various soil types have been developed.